2016
DOI: 10.1186/s40064-016-3004-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neurotoxicity by organophosphate pesticide chlorpyrifos and modulating role of cow urine

Abstract: IntroductionOrganophosphate pesticides are among the most widely used synthetic chemicals for controlling a wide variety of pests and for domestic purposes. Among these chlorpyrifos (CPF) is the most extensively used pesticide throughout the world, including India.ObjectiveThe present study was undertaken to examine the neurotoxicity induced by CPF and modulatory effect of cow urine as a natural antioxidant alternative to reduce the neurotoxic effects of CPF.DesignFor this purpose LD50 was determined and one f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Recent studies showed that people exposed to pesticides are more likely to develop cancer, congenital malformations, infertility problems, neurological problems or weakened immune systems than others ( Sears et al, 2006 ; Badraoui et al, 2007 , 2012 ; Mzid et al, 2017 ). Chlorpyrifos (CPF) is one of the most widely used organophosphorus (OP) in the world for both agriculture and indoor applications ( Sharma and Chadha, 2016 ). The active substance in CPF induces a disruption of nervous system function by inhibition of acetylcholinesterase (AChE), an enzyme that degrades the acetylcholine (Ach) neurotransmitter in both neuromuscular junctions and cholinergic synapses ( Abolaji et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that people exposed to pesticides are more likely to develop cancer, congenital malformations, infertility problems, neurological problems or weakened immune systems than others ( Sears et al, 2006 ; Badraoui et al, 2007 , 2012 ; Mzid et al, 2017 ). Chlorpyrifos (CPF) is one of the most widely used organophosphorus (OP) in the world for both agriculture and indoor applications ( Sharma and Chadha, 2016 ). The active substance in CPF induces a disruption of nervous system function by inhibition of acetylcholinesterase (AChE), an enzyme that degrades the acetylcholine (Ach) neurotransmitter in both neuromuscular junctions and cholinergic synapses ( Abolaji et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in color (from deep violet to light yellow) were read using a spectrophotometer. The optical density was recorded at 517 nm and percentage inhibition was calculated using the formula given below: In vivo studies After range finding, LD 50 value for CPF was found to be 152 mg/ kg body weight using probit analysis software [21], ¼ of LD 50 , i.e., 38 mg/kg b.wt CPF (sublethal dose) was used for experiment and was orally administered to rats using gavage. Three groups of rats were taken which include Group 1 as control treated with corn oil, Group 2 treated with CPF in corn oil, and Group 3 pretreated with AET 1 week before CPF exposure.…”
Section: Determination Of Antioxidant Potential By 2 2-diphenyl-1picmentioning
confidence: 99%
“…The use of exogenous pesticide insecticides often exhibits a stronger insecticidal effect than previous pesticides. As a result, these pesticides have made interesting progress in crop yield, quality and pest resistance [ 8 , 9 ]. Pesticides enter organisms through three main routes: inhalation (lungs), ingestion (mouth), and contact (skin) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, acute OP severe cases also include suicide, homicide and overdose [ 14 ]. At present, chlorpyrifos (CPF) (O, O-diethyl-O -(3,5, 6-trichloro-2-pyridyl) phosphate thioester) is one of the most widely used organophosphorus pesticides globally [ 9 ]. It has been confirmed that CPF can cause oxidative stress damage, which is related to the accumulation of lipid peroxidation products in multiple organs of the body [ 15 ].…”
Section: Introductionmentioning
confidence: 99%